Advances in Computational Plasticity A Book in Honour of D. Roger J. Owen - Oñate, Eugenio; Peric, Djordje; de Souza Neto, Eduardo; Chiumenti, Michele (Computational Methods in Applied Sciences, 2018)
This book brings together some 20 chapters on state-of-the-art research in the broad field of computational plasticity with applications in civil and mechanical engineering, metal forming processes, geomechanics, nonlinear structural analysis, composites, biomechanics and multi-scale analysis of materials, among others. The chapters are written by world leaders in the different fields of computational plasticity.